Recent Advances in the Field of Urinary Tract Infections - Nelius, Thomas (IntechOpen, 2013)
Urinary tract infections (UTI) continue to be under the most common bacterial infections worldwide. Diagnostic and treatment have substantial financial burden on society. In the USA, UTIs are responsible for more than 7 million physician visits annually and about 15% of all community-prescribed antibiotics in the USA are dispensed for UTIs. About 50% of women will experience at least one UTI episode during lifetime, about 1 million emergency department visits due to UTI in the USA alone, resulting in more than 100 000 hospital admissions annually, most often for pyelonephritis. Moreover, UTIs are also the leading cause of hospital-acquired infections, accounting for approximately 40% of all such cases. The majority of these cases are catheter-associated. Therefore, nosocomial UTIs comprise perhaps the largest institutional reservoir for nosocomial antibiotic-resistant pathogens. Beside the economic impact, UTIs affect also significantly the quality of life of the affected population. The aim of this book is to highlight problematic aspects and recent advances in the field of UTIs. The book is divided in three parts.